2001
DOI: 10.1088/0954-3899/27/6/322
|View full text |Cite
|
Sign up to set email alerts
|

B0(s)-B0(s)mixing andbhadron lifetimes from lattice QCD

Abstract: We discuss neutral B s,d meson mixing and b-hadron lifetimes from the perspective of recent lattice calculations. In particular, we consider matrix elements which can be combined with measured ∆M s,d to constrain |V td |, the lifetime ratios τ (Λ b )/τ (B 0 d ) and τ (B − )/τ (B 0 d ) and the lifetime difference, ∆Γ Bs /Γ Bs , in the neutral B s meson system. ‡ Based on talks given by the authors in the UK Phenomenology Workshop on Heavy Flavours and CP Violation, 17th -22nd September 2000, Durham, England.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The other B parameter B S , which is relevant to the B s meson width difference, has also been calculated in the quenched approximation (42,100,(102)(103)(104)(105)(106). The physical result for s / s including next-to-leading-order QCD corrections is 0.074 ± 0.024 (107), which can be compared to the current experimental average 0.07 +0.09 −0.07 (80).…”
Section: B 0 -B 0 Mixing: Quenched Lattice Resultsmentioning
confidence: 89%
“…The other B parameter B S , which is relevant to the B s meson width difference, has also been calculated in the quenched approximation (42,100,(102)(103)(104)(105)(106). The physical result for s / s including next-to-leading-order QCD corrections is 0.074 ± 0.024 (107), which can be compared to the current experimental average 0.07 +0.09 −0.07 (80).…”
Section: B 0 -B 0 Mixing: Quenched Lattice Resultsmentioning
confidence: 89%
“…⊛ Until this year, there was only one lattice study of the matrix elements (2.1), and that one was made in the static limit of HQET [30] (see also ref. [31]). This year, the first lattice QCD computation of ∆B = 0 operators has been performed [32], the main features of which will be explained in the next subsection.…”
Section: Ratios Of the B-meson Lifetimesmentioning
confidence: 99%
“…Some selected reviews in the long history of lattice calculations for the B mixing system can be found in Refs [23,24,25,26,27,28,29,30,31]…”
mentioning
confidence: 99%